AI Integration in Accounting: Operational Efficiency Implications and Ethical Challenges for Professional Accountants - Septarina Prita Dania Sofianti (Oikonomia : Journal of Management Economics and Accounting, 2025)
The development of artificial intelligence (AI) technology has brought fundamental changes in various sectors, including accounting. The integration of AI in accounting practices promises to significantly improve operational efficiency, but on the other hand, it also poses complex ethical challenges for professional accountants. This study aims to explore the impact of AI integration on operational efficiency as well as identify the ethical challenges that arise in the accounting profession. The method used is a systematic literature study with a qualitative approach, which involves searching scientific articles from various accredited databases such as Scopus, ScienceDirect, and ProQuest. The results showed that AI is able to automate routine accounting processes, improve data accuracy, and support real-time financial reporting, which in turn strengthens managerial decision-making. However, challenges such as black box algorithms, potential algorithmic bias, and data privacy and security risks require accountants to have a deep understanding of technology and ethics. The conclusion of this study confirms that the successful integration of AI in accounting is highly dependent on the readiness of human resources, technology governance, and adaptive regulations. The implications of this study lead to the importance of reformulating the accounting education curriculum, increasing accountants' digital competencies, and the need for cross-sector collaboration in building an efficient as well as ethical and accountable technology ecosystem.